Implementation of Professional Development Program for Developing Teachers' Literacy and Numeracy Skills: A Case in Indonesian Context - Anik Maghfiroh (Tadibia Islamika, 2022)
Implementation of quality education requires professional teachers. The former Minister of Religion, Fachrul Razi, released the Madrasah Reform Realizing Education's Promise Program for the first time on 20 October 2020, which until now has been continued by the Minister of Religion Yaqut Cholil Qoumas. This program is long-term and lasts for five years to improve the quality of education management. PKB for educators at the Pekalongan Regency started in 2021. The implementation of the PKB program in KKG activities is carried out with a focus on achieving increased literacy and numeracy skills. The research objectives were: To analyze the teacher's PKB program implementation at KKG in Pekalongan. Analyzing the dynamics of teacher abilities before and after the PKB program at KKG in Pekalongan. Approximate data on the effectiveness of the PKB program implementation in increasing the literacy and numeracy of KKG teachers in Pekalongan. This study uses a mixed method. Data collection through questionnaires, interviews, observation, and documentation. Quantitative data analysis with data quality tests, classical assumptions, simple linear regression analysis, and hypothesis testing is processed through statistical analysis with the help of the SPSS software program. Analysis of descriptive qualitative data with three paths: data reduction, data presentation, and concluding. This research resulted in the findings that teachers are familiar with the material in each learning unit in the PKB module and from the analysis results, the conclusions H1-H4 are accepted. However, the positive correlation is included in the minimal category.